2022
DOI: 10.3389/fbioe.2022.880277
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Corynebacterium glutamicum as the Platform for the Production of Aromatic Aldehydes

Abstract: Graphical Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 60 publications
(97 reference statements)
1
14
0
Order By: Relevance
“…Although a previous pharmacokinetic study showed that PHBA in GE has brain targeting activity during drug distribution (50), its effect and mechanism on transient focal cerebral ischemia remains unclear. At present, PHBA can already be synthesized artificially (51). The preliminary experiment of our research group confirmed that the commercially available PHBA is consistent with the PHBA isolated from GE (52).…”
Section: Discussionsupporting
confidence: 73%
“…Although a previous pharmacokinetic study showed that PHBA in GE has brain targeting activity during drug distribution (50), its effect and mechanism on transient focal cerebral ischemia remains unclear. At present, PHBA can already be synthesized artificially (51). The preliminary experiment of our research group confirmed that the commercially available PHBA is consistent with the PHBA isolated from GE (52).…”
Section: Discussionsupporting
confidence: 73%
“…Albeit lacking a TrpR homolog, C. glutamicum has a putative operator sequence with similarity to the operator DNA binding sequence of the TrpR repressor of E. coli and was detected upstream of the −10 promoter region of the trp operon [26,27]. Transcription of the trp operon is controlled by attenuation and deletion of the leader peptide gene trpL and improved overproduction of L-tryptophan [28] and aromatic aldehydes [29]. Several L-tryptophan-producing C. glutamicum strains have been developed [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Another biosynthetic pathway for 3,4-DHBA production was proposed through the end product of the common aromatic pathway chorismate [8] (Figure 1). This biosynthetic route includes more reactions than 3,4-DHBA synthesis via DSD reaction but has other advantages [8]. DSDs are a diverse group of enzymes, which are subdivided into four classes: bacterial single-domain, fungal single-domain, bacterial two-domain, and bacterial membrane-associated enzymes [9].…”
Section: Introductionmentioning
confidence: 99%
“…DHS is an intermediate of the common aromatic pathway ( Figure 1 ), and the DSD reaction allows to synthesize 3,4-DHBA from glucose [ 7 ] ( Figure 1 ). Another biosynthetic pathway for 3,4-DHBA production was proposed through the end product of the common aromatic pathway chorismate [ 8 ] ( Figure 1 ). This biosynthetic route includes more reactions than 3,4-DHBA synthesis via DSD reaction but has other advantages [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation